Integral Assessment of the Development Level of Electronic Business in the Regions of the Volga Federal District - M. V. Bikeeva; K. V. Belash (Статистика и экономика)
Purpose of the study. Information and communication technologies are becoming a powerful tool for the development of electronic business. Today, the leaders in the global economic and political space are precisely those countries that have learned to determine the vector of development of information technologies and use new opportunities for their application. The development of innovative digital technologies in Russia and in the world is widely discussed in the framework of various discussion platforms. In particular, at the International Forum “The Digital Future of the Global Economy” (January 31, 2020 Almaty), digitalization of trade processes between the EAEU membercountries became one of the main topics. The annual Tech Week conference (Moscow) is becoming a traditional place for discussing the implementation of innovative technologies in business, as well as for the exchange of experience of leading Russian and world corporations in the field of electronic business. In this regard, there is a need for a comprehensive statistical assessment of the development level of electronic business of the territory.Materials and methods. The research was based on the data of the Federal State Statistics Service for 2018 for the regions of the Volga federal district, and the results of monitoring the development of the information society in the Russian Federation. As a tool for assessing the degree of digitalization of business in the regions of the Volga federal district, the graphic polygon (radar) method is used.Results. The article provides a retrospective analysis of the stages of development of electronic business in Russia. Among the characteristic features of the modern stage of its development are the mass introduction of Internet technologies and the transformation of traditional business methods. The introduction of advanced information and communication technologies contributes to greater involvement of the business sector in electronic business. In terms of the level of development of information and communication technologies (ICT Development Index), Russia ranks 45th among the countries of the world. For the period 2010 - 2018 the development of electronic business in Russia has a positive trend. According to the results of 2018, the volume of the Russian e-commerce market amounted to 1280 billion rubles, or 4.1% of the total trade turnover. According to forecast estimates, by 2023 the volume of Russian e-commerce market will grow to 8.5% of the total turnover and amount to 2780 billion rubles. An integrated assessment of the development level of electronic business was carried out according to sixteen local criteria. As a result of calculating the private and local ranks of the values of the relevant criteria, fourteen polygons of the level of development of electronic business were constructed by the number of regions of the Volga federal district. The results obtained allow us to state the existence of a high degree of heterogeneity of the regions of the Volga federal district according to the integral indicator under study. Among the leading regions in terms of electronic business development are the Republic of Tatarstan, Perm krai and Nizhny Novgorod region. Outsider regions – the Mari El Republic, the Republic of Mordovia, and the Kirov region – are characterized by a low percentage of organizations that used the capabilities of the Intranet and Extranet, the absence of special software for managing sales of goods (works, services), and limited use of software, in particular ERP, CRM and SCM systems.Conclusion. The widespread use of information and communication technologies entails the expansion of opportunities and improving the quality of coordination of business activities. We should remember that if modern business cannot quickly adapt to the new requirements of the digital economy, then it risks becoming uncompetitive. The results of the study revealed a differentiation in the development of electronic business in the regions of the Volga federal district. A similar situation is observed in most constituent entities of the Russian Federation and is due in many respects to specific reasons for each region. The timely fulfillment of the goals and objectives of digital transformations in the Russian Federation reflected in the Digital Economy of the Russian Federation Program and other regulatory documents will help to smooth out the existing imbalances.